Respuestas
Respuesta dada por:
2
f(x) = 2x/3 + 1/2
f(-3/4) = -2(-3/4)/3 +1/2
f(-3/4) =(6/4 )/3+1/2
f(-3/4) = (3/2)/3 + 1/2
f(-3/4) = 3/6 + 1/2
f (-3/4) = 1/2 +1/2
f( -3/4) = 2/2
f( -3/4) = 1
f(-3/4) = -2(-3/4)/3 +1/2
f(-3/4) =(6/4 )/3+1/2
f(-3/4) = (3/2)/3 + 1/2
f(-3/4) = 3/6 + 1/2
f (-3/4) = 1/2 +1/2
f( -3/4) = 2/2
f( -3/4) = 1
Respuesta dada por:
4
Si: ![f(x) = \frac{-2x}{3} + \frac{1}{2} f(x) = \frac{-2x}{3} + \frac{1}{2}](https://tex.z-dn.net/?f=f%28x%29+%3D++%5Cfrac%7B-2x%7D%7B3%7D++%2B++%5Cfrac%7B1%7D%7B2%7D+)
Entonces, para x = -3/4 , tendremos que:
![f(x) = f( \frac{-3}{4} ) = \frac{-2(-3/4)}{3} + \frac{1}{2} f(x) = f( \frac{-3}{4} ) = \frac{-2(-3/4)}{3} + \frac{1}{2}](https://tex.z-dn.net/?f=f%28x%29+%3D+f%28+%5Cfrac%7B-3%7D%7B4%7D+%29+%3D++%5Cfrac%7B-2%28-3%2F4%29%7D%7B3%7D++%2B++%5Cfrac%7B1%7D%7B2%7D+)
![f(x) = f( \frac{-3}{4} ) = \frac{3/2}{3} + \frac{1}{2} f(x) = f( \frac{-3}{4} ) = \frac{3/2}{3} + \frac{1}{2}](https://tex.z-dn.net/?f=f%28x%29+%3D+f%28+%5Cfrac%7B-3%7D%7B4%7D+%29+%3D++%5Cfrac%7B3%2F2%7D%7B3%7D++%2B++%5Cfrac%7B1%7D%7B2%7D+)
![f(x) = f( \frac{-3}{4} ) = \frac{3}{6} + \frac{1}{2} f(x) = f( \frac{-3}{4} ) = \frac{3}{6} + \frac{1}{2}](https://tex.z-dn.net/?f=f%28x%29+%3D+f%28+%5Cfrac%7B-3%7D%7B4%7D+%29+%3D++%5Cfrac%7B3%7D%7B6%7D++%2B++%5Cfrac%7B1%7D%7B2%7D+)
OJO: 3/6 = (3*1)/(3*2) = 1/2
![f(x) = f( \frac{-3}{4} ) = \frac{1}{2} + \frac{1}{2} f(x) = f( \frac{-3}{4} ) = \frac{1}{2} + \frac{1}{2}](https://tex.z-dn.net/?f=f%28x%29+%3D+f%28+%5Cfrac%7B-3%7D%7B4%7D+%29+%3D++%5Cfrac%7B1%7D%7B2%7D++%2B++%5Cfrac%7B1%7D%7B2%7D+)
← Respuesta
Eso es todo!! Saludos!
Entonces, para x = -3/4 , tendremos que:
OJO: 3/6 = (3*1)/(3*2) = 1/2
Eso es todo!! Saludos!
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años